Expressing, Responding, Protecting, and Inspiring through Art - Molly Bathje MS, OTR/L (Scholarworks @ WMU, 2013)
Margy Hunter, MS, MA, LLP, OTR/L, created the cover of the Spring 2013 issue of The Open Journal of Occupational Therapy. She created this untitled work as a personal reflection on the impact of war on individuals and society, as well as on the history of the profession of occupational therapy (OT), which began in response to military service members' needs. Also embedded in the creation of this piece are the restorative benefits of participation in creative arts for OT practitioners who deliver services to patients experiencing profound life changes. Additionally, this article explores the artists' use of art in OT practice to create occupational environments in her community, and as a tool to support her own occupational functioning.